Sentimientos de un desesperado (1692) (trad. del italiano por Dolores Ocaña y Attilio Manzi) [pp. 209-213]. - Vico, G. (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 4 (1994). 244 págs. ISBN 1130-7498